2013
DOI: 10.1152/ajpheart.00883.2012
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of autologously derived mitochondria protects the heart from ischemia-reperfusion injury

Abstract: Mitochondrial damage and dysfunction occur during ischemia and modulate cardiac function and cell survival significantly during reperfusion. We hypothesized that transplantation of autologously derived mitochondria immediately prior to reperfusion would ameliorate these effects. New Zealand White rabbits were used for regional ischemia (RI), which was achieved by temporarily snaring the left anterior descending artery for 30 min. Following 29 min of RI, autologously derived mitochondria (RI-mitochondria; 9.7 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
498
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(534 citation statements)
references
References 40 publications
33
498
2
1
Order By: Relevance
“…The benefits of compensatory endogenous mitochondrial transfer through extracellular spaces into metabolically compromised cells in a variety of prevalent acquired diseases provided the impetus for investigating mitochondrial transplantation as a viable treatment approach by our laboratory as well as by other groups 26. To determine whether transplantation of polymer‐functionalized mitochondria was capable of triggering a bioenergetic switch in cells of varying origin and phenotype, simultaneous OCR and ECAR were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of compensatory endogenous mitochondrial transfer through extracellular spaces into metabolically compromised cells in a variety of prevalent acquired diseases provided the impetus for investigating mitochondrial transplantation as a viable treatment approach by our laboratory as well as by other groups 26. To determine whether transplantation of polymer‐functionalized mitochondria was capable of triggering a bioenergetic switch in cells of varying origin and phenotype, simultaneous OCR and ECAR were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Autologous mitochondria were injected into a rabbit model of regional ischemia and improved recovery from the injury (Masuzawa et al, 2013). Data showed that most of the injected mitochondria remained extracellular with some mitochondria taken up by cells, although it was unclear how mitochondria were taken up from the extracellular fluid (Masuzawa et al, 2013). …”
Section: Direct Uptake By Co-culture With Isolated Mitochondriamentioning
confidence: 99%
“…Additionally, the LAD is occluded just distal to the first diagonal. 127,128 The intervention can be performed at any time point but commonly occurs just before and after reperfusion.…”
Section: Acute Coronary Occlusion Modelsmentioning
confidence: 99%